Effects of loading and aging on attentional demands of postural control - Ong, Yi Min. (2010)
It has traditionally been considered that postural control is an automatic or reflex controlled task, suggesting that postural control systems use minimal attentional resources. However, recent research has provided evidence against this assumption. These studies suggest that there are significant attentional requirements for postural control, and that these requirements vary depending on the postural tasks, the ages of the individuals and their balance abilities.